Utilization of Eco-enzymes from Citrus Peels and Pineapple Peels Waste as Detergent LAS Remediation Agent - Gaspersz, Marce Monica; Fitrihidajati, Herlina (LenteraBio : Berkala Ilmiah Biologi, 2022)
Linear Alkylbenzena Sulfonate (LAS) is one of the largest pollutants in the water. This study was aimed to determine: (1) the characteristics of eco-enzymes from citrus peels and pineapple peels waste. (2) the effect of using eco-enzymes at various consentration in decreasing LAS levels and water quality. (3) the optimal concetration of eco-enzymes in decreasing LAS levels and water quality. This study was an experimental using Randomized Completely Design with one treatment factor, namely the concentration of eco-enzymes at 0%, 5%, and 10% for 5 days. The study was conducted at the Ecology Laboratory, Biology, FMIPA Unesa. There are two stages of study, namely, the stage of making ecoenzymes with the parameters measured in the form of pH, temperature, and TDS. The implementation phase with the measured parameters in the form of LAS levels and water quality (DO, BOD, pH, temperature, and TDS). The first stage of data analysis technique was carried out in a quantitative descriptive manner, while the second stage included the LAS level parameter which was carried out statistically using one-way ANOVA followed by Duncan’s test. Then the result refers to PERGUB JATIM No. 72 of 2013 and water quality parameters using quantitative descriptive. The results of the study showed: (1) the characteristics of the ecoenzyme had a mean pH (3.69), temperature (26.8)?, and TDS of 1308 ppm. (2) various concentrations of ecoenzymes affect the decrease in LAS levels and water quality. LAS levels from high to low were 0% (8.30 ppm), 10% (7.00 ppm), and 5% (5.90 ppm). DO water quality 0% (4.02 ppm), 5% (1.43 ppm), 10% (1 ppm); BOD 0% (1.19 ppm), 5% (0.54 ppm), 10% (0.77 ppm); pH 0% (7.20), 5% (6.11), 10% (5.30); temperature 0% (26.73?), 5% (26.76?), 10% (26.8?); and TDS 0% (0.65 ppm), 5% (242.16 ppm), 10% (409.66). (3) 5% concentration is more optimal in reducing LAS levels, but still above the specified quality standard, which is 3 ppm.